Pain and delirium: mechanisms, assessment, and management - Sampson, Elizabeth L.; West, Emily; Fischer, Thomas (European Geriatric Medicine, 2020)
Abstract Purpose Pain and delirium are common problems for older people. Both conditions are prevalent in acute hospital settings. In people living in the community, delirium often precipitates presentation to the emergency department. Pain and delirium are known to interact in a complex and multidirectional way. This can make it challenging for staff to recognize and treat pain in people with delirium. Methods This paper aims to explore the complex relationship between pain and delirium and on pain assessment in delirium, drawing together evidence from a range of settings including acute medical, cardiac and orthopaedic post-operative cohorts, as well as from aged care. Results A limited number of studies suggest there is an association between pain and delirium; however, this is a complex, particularly where analgesics which may-themselves cause delirium are prescribed. Factors acting on the pathway between pain and delirium may include depression, sleep deprivation and disturbance of the cholinergic system. Delirium affects the ability to self-report pain. The fluctuating nature of delirium as well as reduced awareness and attention may challenge practitioners in recognizing, assessing and treating pain. Evidence concerning the reliability and validity of current observational and self-assessment tools in people with delirium is unclear but some show promise in this population. Conclusion The current evidence base regarding assessing pain in people with delirium is lacking. Tentative recommendations, drawing on current guidelines require robust testing. Guidelines for people with pain and dementia require adaptations regarding the unique characteristics of delirium. The complex interplay between dementia, pain and delirium warrants further investigation across a range of settings.